Pragmatic functions of Indonesian in the column “smart traveler” of the Bali tribun newspaper - Ni Putu Evi Wahyu Citrawati; I Wayan Teguh; Ni Putu N. Widarsini (English, 2020)
This study aims to see the politeness of Indonesian in a printed daily newspaper published in Bali, namely the daily Tribun Bali which presents a page of a column called "Smart Traveler" that discusses tourism objects in Bali. In this study, two points were researched, namely the form of politeness and the form of Indonesian politeness based on the principle of politeness (Leech, 1993). Data obtained naturally by reading the daily Tribun Bali, especially the tourism column "Smart Traveler". Then the data is coded according to the function of the Indonesian language, especially in the field of pragmatics concerning the principle of politeness, and transcribed on the data card. The data then were analyzed using two aspects, namely, first, the data were analyzed to determine linguistic elements such as phonology, morphology, syntax, semantics, and pragmatics in a predetermined time. Second, the data were analyzed and presented descriptively, then the results obtained were viewed from a theoretical perspective to find out why that was all that happened. In analyzing the data, the distributional method is used, which is working within the scope of the language itself without connecting things outside it.